2004
DOI: 10.1111/j.1365-313x.2004.02265.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of TIP1;1 aquaporin in Arabidopsis leads to cell and plant death

Abstract: SummaryArabidopsis TIP1;1 (cTIP) is a member of the tonoplast family of aquaporins (AQP). Using RNA interference (RNA i ) we reduced TIP1;1 to different extent in various lines. When most severely affected, miniature plants died, a phenotype partially complemented by the TIP1;1 homolog McMIP-F. Less severely affected lines produced small plants, early senescence, and showed lesion formation. The relative water content in TIP1;1 RNAi plants was not significantly affected. Global expression profiling suggested a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
3
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 46 publications
3
85
3
2
Order By: Relevance
“…At the metabolic level, mutants accumulated starch and showed changed sugar content. Based on their results, Ma et al (54) suggested that TIP1;1 may have a role in vesicle trafficking to the central vacuole and vesicle-based metabolite routing in the cell. Thus, they suggested a unique function of TIP1;1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the metabolic level, mutants accumulated starch and showed changed sugar content. Based on their results, Ma et al (54) suggested that TIP1;1 may have a role in vesicle trafficking to the central vacuole and vesicle-based metabolite routing in the cell. Thus, they suggested a unique function of TIP1;1.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, down-regulation of TIP1;1 by RNA interference technology in Arabidopsis resulted in a strong and complex phenotype of early senescence and death (54). F 1 mutants were classified according to the level of expression of the RNA interference construct, which correlated well with the severity of the phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…For additional discussions of genes that function in phloem loading and carbon partitioning (e.g. H + -ATPase, K + channel, Suc synthase, aquaporins), we refer interested readers to the following articles (Nolte and Koch, 1993;DeWitt and Sussman, 1995;Hannah et al, 2001;Deeken et al, 2002;Dinges et al, 2003;Ma et al, 2004;Hardin et al, 2006;Lu and Sharkey, 2006;Smith and Stitt, 2007).…”
mentioning
confidence: 99%
“…The selectivity filter of AqpZ is the narrowest point in it's water channel, it is formed by the side chains of Phe43, His174, Arg189 and the carbonyl of Thr183,the water in channel forms hydrogen-bond to the carbonyls of T183 (Savage et al 2003). AQGPs usually have Trp-GlaPhe-Arg, some AQGPs have His (Phe)-Ile(His)-Ala(Thr)-Val (Ma et al 2004), their selectivity filters usually are more hydrophobic than in AQPs. GlpF has a much lower conductivity for water than to water channels, the selectivity filter is formed by Trp48, Gla191, Phe200 and Arg206, the phenyl ring of Phe200 and the indole of Trp48 form the hydrophobic corner, they have Van der Waals interaction with the alkyl chain of glycerol, and successive hydroxyl groups form hydrogen bonds with Arg206 and Phe200, and groups of several other amino acids (Fu et al 2000).…”
Section: Structure Analysis Of Gjtipmentioning
confidence: 99%
“…Chilling treatment caused a decrease in the transcript level of OsTIP1;1 in roots, the decreased mRNA levels of OsTIP1;1 were recovered 9 h after warming. Using RNA interference(RNAi), Ma (Ma et al 2004) reduced AtTIP1;1 to different extent in various Arabidopsis lines, when most severely affected, miniature plants died, less severely affected lines produced small plants, early senescence, and showed lesion formation. Analysis of global expression profiling and metabolite profiles suggest a function for TIP1;1 in vesicle-based metabolite routing through or between pre-vacuolar compartments and the central vacuole.…”
Section: The Transcriptional Expression Of Gjtipmentioning
confidence: 99%